ГЕРМЕНЕВТИКА МЕТАФОРИ - Дубініна Віра Олександрівна (International Journal of Innovative Technologies in Social Science, 2020)
The possibilities of philosophical hermeneutics in connection with the problems of interpretation and understanding of metaphors are examined. The hermeneutic method and its use in the analysis of specific semantic formations is associated with the concept of metaphor, which can be considered as the most important component of hermeneutic discourse. The metaphor and its capabilities are an essential characteristic of language and speech activity, reflecting the creative nature of our consciousness, the very structure of rationality. Various theoretical approaches to understanding metaphors are analyzed. Criticism of metaphors continues to the present. It seems to many researchers that metaphors, trails, idioms are illegitimate children of knowledge, rationality, and language. This is quite typical for representatives of modern empiricism, nominalism, reductionism, skepticism, etc., which are driven, in general, by good motivation. This is an attempt to achieve at least conditional objectivity, accuracy and reliability of the results in our humanitarian knowledge, for which, of course, we should bring the language of philosophy closer to the language of nature sciences. True, it has long been noted that this notorious and exacted “accuracy” is not at all true or true, the correct reflection of the objects studied, such as culture, morality, truth or poetry. Oddly enough, getting rid of metaphors, we can not say anything more true, and just something non-trivial about poetry, such that it really clarifies its essence or simply explains to us why people write and read poetry. Another approach that we can already find with Aristotle, and implicitly among the pre-Socratics, not to mention Plato, is to recognize the metaphor as the most important role in our language and knowledge. The fact that no language can do without metaphors is quite obvious. But is metaphor so important for our knowledge? We strive to present the point of view according to which the metaphor is an instrument of cognitive activity and, as a consequence, of the knowledge of the world by man, no less than logic or mathematics, not to mention the empirical methods of the natural sciences. Even a preliminary examination of the role of metaphor in hermeneutic discourse shows that it is a metaphor, more generally, metaphorical, and in another aspect, idiomaticity, that creates the very possibility for hermeneutics to exist. It is metaphors with their ambiguity that provoke interpretation and cognition using the hermeneutic method. Even a single metaphor creates a certain semantic tension, which can only be resolved through the effort of interpretation. A text that is fundamentally built or consists mainly of metaphors creates a special semantic space in which the hermeneutic consideration realizes itself. In a sense, these are approximately coincident regions, wherever we meet with a metaphor, hermeneutics also becomes possible. The reverse is also partly true, the task of hermeneutic discourse is not only the interpretation of explicit metaphors, but also the discretion of metaphorical or idiomatic where it is not at first glance visible. It cannot be argued that the search for metaphors is the only thing of hermeneutics, however, it is also true that without considering the tropes, modern hermeneutics would have a completely different look and purpose.